The gendered experiences of women, men and couples who plan, have and narrate homebirths - Daniels, Nicole Miriam (Department of Sociology, 2016)
In South Africa excellent scholarship exists on women's experiences of homebirth but no studies have yet examined men's or couples' experiences. The thesis sought to make a valid contribution by uncovering a relational view of homebirths that made sense of the gendered interactions and relational negotiations of women, men and couples who experienced homebirth. It adopted a longitudinal, qualitative approach based on thirty interviews with five couples before and after homebirth. Dyadic interviewing and the listening guide offered relational methods of collecting and analysing data that additionally engaged the researcher in highly reflexive modes of producing knowledge. By foregrounding the relational context, narrative constructions of homebirths showcased simultaneous operations of gender as both opportunity and constraint. This study uncovered the active social processes involved in couples' decision making narratives and the relational interactions in their homebirth experiences. Joint narratives of homebirth displayed the interconnectedness of relating-selves where couples' relational scripts were brought to bear on the meanings of homebirth. Women and men found meaning in their experiences through connection with others; men privileged a selfless masculinity and women a self-reliant femininity. Both positioned women's relationship to their body and thus their baby as central to homebirth. Through in-depth scrutiny of the practice of homebirths, this study detailed how intimate interpersonal relationships are shaped by broader social and gendered processes.